2018
DOI: 10.1016/j.pjnns.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic medulla compression by vertebral artery

Abstract: VAMCS should be considered as the cause of neurological deficits when other pathological entities are ruled out. In symptomatic conflict of the VA with the medulla, microvascular decompression using a Gore-Tex implant can be an effective method of treatment. Nevertheless, a statistical analysis on all reported cases showed favorable results using the VA repositioning technique when compared with MVD (success rate 91% vs. 58%, p<0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One longitudinal study revealed an accelerated rate of WM impairment in brainstem and subcortex in PD compared with normal aging-related WM alterations [26]. Both subclinical and symptomatic neurovascular compression of the brainstem-caused WM alterations have been identified in VBD [12,13]. Moreover, local and widespread neurovascular compression-related WM diffusion alterations have been reported in trigeminal neuralgia [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One longitudinal study revealed an accelerated rate of WM impairment in brainstem and subcortex in PD compared with normal aging-related WM alterations [26]. Both subclinical and symptomatic neurovascular compression of the brainstem-caused WM alterations have been identified in VBD [12,13]. Moreover, local and widespread neurovascular compression-related WM diffusion alterations have been reported in trigeminal neuralgia [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VBD is about 0.05-6.48% in general population [10,11]. Subclinical and symptomatic brainstem WM impairments are discovered in VBD [12,13], and dolichoectasia are associated with widespread WM hyperintensity in ischemic stroke [14]. Despite VBD is rarely described in PD, the shared patterns involving neurovascular changes, brainstem involvement and widespread WM alterations suggest a possible association between VBD and PD.…”
Section: Introductionmentioning
confidence: 99%
“…MVD is done by using a separating material placed between the vertebral artery and compressed brainstem, but may not be as satisfactory as vertebral artery repositioning method with anchoring/sling to the adjacent dura. 15…”
Section: Discussionmentioning
confidence: 99%
“…MVD is done by using a separating material placed between the vertebral artery and compressed brainstem, but may not be as satisfactory as vertebral artery repositioning method with anchoring/sling to the adjacent dura. 15 Medullar compression by non-dolichoectatic vertebral artery is a diagnosis of exclusion when no incriminating lesion is found in brainstem or cranial nerve features. However, the possibility of vertebrobasilar transient ischemic attacks (TIAs) as a cause of these symptoms cannot be totally ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…9 Following these 2 early descriptions of Vertebral Artery Medullary Compression Syndromes (VAMCS), there have been about 33 reports of MCS reported till now with varying symptomatology ( Table 1). The atypical symptoms other than hemiparesis and hypertension ascribed to VAMCS are Cranial neuropathies, 10 palatal myoclonus, 11 diplopia, 12 quadriplegia, 13 episodic dysarthria, 14 respiratory failure, 15 hypoesthesia, 16 and rare variant syndromes like Opalski 17 and Rabbit syndromes. 18 Our patient had long standing dizziness and nystagmus most likely due to the compression of the vestibular nuclei and its connections.…”
Section: Discussionmentioning
confidence: 99%